The Impact of Self-Esteem on Adolescent Girls Victims of Bullying in Islamic Boarding Schools - Nadzifah Fiddiana; Annisa Triana Jhonatha; Amalia Ahmad (CV. Syntax Corporation Indonesia, 2024)
Self-esteem is a self-assessment carried out by oneself. The assessment reflects an attitude of acceptance and rejection and shows how far an individual believes he or she is capable, important, successful and valuable. The purpose of this study is to describe the picture of self-esteem in late adolescent girls who are victims of bullying. The research method uses a qualitative approach with descriptive analysis methods with in-depth interview techniques and non-participant observation. The results of the study found that bullying negatively impacts adolescent self-esteem.